2012
DOI: 10.1016/j.phymed.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Pueraria root extract (Pueraria lobata) ameliorates impaired glucose and lipid metabolism in obese mice

Abstract: The incidence of type 2 diabetes and metabolic disease is rapidly increasing, but effective therapies for their prevention and treatment have been poorly tolerated or minimally effective. In this study, chronic administration of kudzu root extract (8 months, 0.2% w/w in diet) decreased baseline fasting plasma glucose (183±14 vs 148±11 mg/dl) and improved glucose and insulin tolerance in C57BL/6J ob/ob mice (1.67±0.17 ng/ml [kudzu treated] vs. 2.35±0.63 ng/ml [control]), but such treatment did not alter these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 28 publications
6
53
0
Order By: Relevance
“…The T max of puerarin (approximately 0.5 hours) was much shorter [36] than those of daidzein, genistein, and their glucosides. Prasain et al [9] also hypothesized that the sodium-dependent glucose transporter (SGLT) is involved in the transport system of puerarin in a rat model [31][32][33]. The rapid absorption of puerarin in our study might be attributable to the absorption from the small intestine via SGLT.…”
Section: Biokinetics Of Kudzu Isoflavonessupporting
confidence: 48%
See 2 more Smart Citations
“…The T max of puerarin (approximately 0.5 hours) was much shorter [36] than those of daidzein, genistein, and their glucosides. Prasain et al [9] also hypothesized that the sodium-dependent glucose transporter (SGLT) is involved in the transport system of puerarin in a rat model [31][32][33]. The rapid absorption of puerarin in our study might be attributable to the absorption from the small intestine via SGLT.…”
Section: Biokinetics Of Kudzu Isoflavonessupporting
confidence: 48%
“…A previous report indicated that nonmetabolized puerarin and a small amount of its glucuronide were detected in the serum of rats orally administered puerarin [31]. Moreover, Prasain et al [9] demonstrated that puerarin was widely distributed (kidney, liver, lung, pancreas, heart, eye, and brain) in rats orally administered puerarin [31][32][33]. Hence, almost all puerarin presumably is absorbed from the intestine, enters into the systemic circulation, and is distributed in the tissues without deglycosylation and conjugation.…”
Section: Biokinetics Of Kudzu Isoflavonesmentioning
confidence: 97%
See 1 more Smart Citation
“…Dried kudzu roots (Puerariae radix) are traditionally used in Asian countries, including Japan, as an herbal medicine to treat the common cold, headaches, diarrhea, and hypertension. Prasain et al demonstrated that kudzu root extract ameliorated impaired glucose and lipid metabolism in obese male mice (6). They also reported that in addition to lowering arterial blood pressure, a kudzu root extract diet significantly reduced blood cholesterol, glucose, and insulin levels in stroke-prone spontaneously hypertensive rats (7).…”
mentioning
confidence: 99%
“…It has been reported that puerarin improved insulin resistance and glucose tolerance (Prasain et al 2012), protected pancreatic islet from hydrogen peroxide-induced b-cell damage (Xiong et al 2006) and lowered blood glucose level in mice challenged with streptozotocin (STZ) (Hsu et al 2003), via promoting glucose uptake by skeletal muscle and adipocytes (Hsu et al 2003, Lee et al 2010 and attenuating glucose and insulin response (Prasain et al 2012). However, there is a lack of understanding of whether puerarin can act on insulin-producing b-cell and improve its function and survival.…”
Section: Introductionmentioning
confidence: 99%